2009
DOI: 10.1186/1471-2180-9-221
|View full text |Cite
|
Sign up to set email alerts
|

Subgingival bacterial colonization profiles correlate with gingival tissue gene expression

Abstract: BackgroundPeriodontitis is a chronic inflammatory disease caused by the microbiota of the periodontal pocket. We investigated the association between subgingival bacterial profiles and gene expression patterns in gingival tissues of patients with periodontitis. A total of 120 patients undergoing periodontal surgery contributed with a minimum of two interproximal gingival papillae (range 2-4) from a maxillary posterior region. Prior to tissue harvesting, subgingival plaque samples were collected from the mesial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 43 publications
3
92
0
1
Order By: Relevance
“…Excellent correlation of array data and confirmatory qPCR was shown previously (Papapanou et al, 2009). …”
Section: Methodsmentioning
confidence: 92%
“…Excellent correlation of array data and confirmatory qPCR was shown previously (Papapanou et al, 2009). …”
Section: Methodsmentioning
confidence: 92%
“…Despite this, no unique pathogen has been found yet corresponding to the postulate modified by HenleKoch (21). Partly, the criteria have been met due to the fact that it's possible for periodontium to be infected by P.gingivalis (17) and immunisation against this pathogen prevents the development experimental periodontitis in the same animal model (17,23).…”
Section: Etiologymentioning
confidence: 99%
“…Research shows significant genetic impact on the antibiotic sensitivity in patients with CP (21). Genetic factors trigger immune reactions as a whole.…”
Section: Etiologymentioning
confidence: 99%
“…We demonstrated that distinct patterns of subgingival microbial colonization associate with discernible gene expression signatures in the adjacent gingival 653588J DRXXX10.1177/0022034516653588Journal of Dental ResearchMaster Regulator Genes in Human Periodontitis research-article2016 tissues (Papapanou et al 2009). Despite limited molecular differences among lesions from chronic or aggressive periodontitis (Kebschull et al 2013), gingival tissue transcriptomes identified 2 clusters of patients (Kebschull et al 2014) who differed with respect to periodontitis extent and severity, levels of specific subgingival microbiota, and serum IgG antibody responses to selected bacteria.…”
Section: Introductionmentioning
confidence: 99%